Overview of the Causes of BPJS Health Pending Claims Due to Inaccuracy of Diagnosis Codes in Sebelas Maret University (UNS) Hospital - Bella, Cindy Rozza; Pratama, Aldi; Abidin , Arif Zaenal (Procedia of Engineering and Life Science, 2024)
In submitting a BPJS Health claim, not all submitted documents can be claimed. Claim status is declared ineligible or pending. A pending claim occurs if the claim file submitted by the hospital is incomplete or does not comply with the requirements set by BPJS Health. Delayed claims can disrupt hospital cash flow and cause losses for the hospital and BPJS Health participants. This research aims to describe the causes of pending claims at UNS Hospital. This research is a quantitative descriptive study with a population of 182 inpatients pending claim documents at UNS Hospital for the period August-October 2023. The sample for this research is 78 pending claim documents based on diagnosis code verification. The sampling technique is total sampling. Based on the data obtained, the number of documents with coding confirmation is 78 pending claim documents s or 11.3% of the total pending claims in the period August – October 2023. This data shows that the majority of pending claim documents are due to inaccurate diagnosis. The factor causing pending claims from BPJS Health inpatients at UNS Hospital occurs due to differences in perception between hospital staff and BPJS Health and is not purely due to coder error, but due to a lack of supporting data as a diagnosis enforcer which affects the accuracy of the code.